The Representation of Islamic Identity in al-Marjani’s Poetry in Mustafād al-Akhbār: A Study in ʿIlm al-Maʿānī - Taqiyah Syamsul Arifin Abdul Lathif; Laily Fitriani; Halimi Halimi (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2025)
This article examines the representation of Islamic identity in the poetry of Shihabuddin al-Marjani as presented in Mustafād al-Akhbār, employing a balāghah-based approach grounded in ʿilm al-maʿānī. The study addresses the limited scholarly attention given to rhetorical meaning (maʿnā) as a key mechanism through which Islamic identity is articulated in classical Muslim poetry within marginal socio-political contexts. The objective of this research is to explain how linguistic structures and rhetorical strategies in al-Marjani’s poetry convey Islamic values within the socio-political setting of the Volga-Tatar region. Methodologically, the study applies qualitative textual analysis to two selected poems that represent two distinct dimensions of identity construction: Islam as a constructive intellectual force and Islam as a historically wounded identity. The analysis focuses on major balāghī devices, including khabariyyah and insyāʾiyyah sentence structures, iltifāt, muqābalah, and taqdīm, examining their semantic and pragmatic functions. The findings reveal that these rhetorical devices are strategically employed to produce ethical, emotional, and symbolic meanings that reinforce Islamic consciousness amid cultural and colonial crises. This study contributes to Arabic literary studies and Islamic intellectual history by demonstrating the significance of ʿilm al-maʿānī in uncovering the ideological and identity-forming roles of poetry, particularly in non-Arab Islamic contexts under colonial pressure.